Leadership Lessons from Six Seasons of "Community" - Kim Nehls (Academic Chairpersons Conference Proceedings, 2019)
During five seasons of the NBC sit-com Community (2009-2015) and an additional season on Yahoo (2016), Americans discovered the academics and antics of Greendale Community College. The TV show centered around seven diverse students who formed a study group in the pilot episode and eventually morphed into a tight-knit family that worked and played together beyond graduation. Five student development theories are relevant to Community. Come to this session to see how lessons will be applied to examples from the show.
Keywords: pop culture; higher ed; TV; leadership